Strategic Management and Artificial Intelligence in Enhancing Competitiveness of Islamic Educational Institutions: A Systematic Literature Review - Auni Luthfiah Nurfathina; Oki Dermawan; Muhammad Anas Maarif; Desmia Evi Dati (re-JIEM (Research Journal of Islamic Education Management), 2026)
In the era of digital disruption, Islamic educational institutions face the challenge of enhancing competitiveness while preserving Islamic educational values. This study aims to analyze the integration of strategic management and artificial intelligence (AI) in strengthening the competitiveness of Islamic educational institutions through a systematic literature review. Following a structured literature search protocol across academic databases and institutional repositories, 50+ peer-reviewed articles, policy reports, and scholarly publications from 2020 to 2026 were selected and analyzed using thematic content analysis. The findings reveal that the synergy between structured strategic management and AI adoption significantly enhances institutional competitiveness through data-driven planning, curriculum innovation, administrative efficiency, and adaptive transformational leadership. However, implementation remains constrained by limited digital infrastructure, gaps in AI literacy among human resources, and weak performance-based evaluation cultures. This study emphasizes that sustainable competitive advantage is achieved when Islamic educational institutions align modern governance, transparent management practices, and the internalization of Islamic values as a core value proposition. The findings offer a conceptual framework and practical recommendations for institutional leaders and policymakers to design adaptive, sustainable, and quality-oriented digital transformation strategies.